Antimicrobial Resistance, Virulence Gene Profiling, and Spa Typing of Staphylococcus aureus Isolated from Retail Chicken Meat in Alabama, USA - Rawah Faraj; Hazem Ramadan; Kingsley E. Bentum; Bilal Alkaraghulli; Yilkal Woube; Zakaria Hassan; Temesgen Samuel; Abiodun Adesiyun; Charlene R. Jackson; Woubit Abebe (Pathogens)
Antibiotic-resistant Staphylococcus aureus (S. aureus) in retail meat poses a public health threat requiring continuous surveillance. This study investigated the frequency of isolation, toxin genes, and antibiotic resistance profile of S. aureus recovered from retail poultry meat samples and presented results beneficial to public health interventions. Of 200 samples collected, 16% (32/200) tested positive for S. aureus, and these were recovered from thigh 37.5% (12/32), wing 34.4% (11/32), gizzard (15.6% (5/32), and liver 12.5% (4/32) samples. Findings of spa typing analysis revealed that 68.8% (22/32), 18.8% (6/32), 9.4% (3/32), and 3.0% (1/32) of the isolates belonged to the spa types t267, t160, t548, and t008, respectively. For antibiotic susceptibility testing, 12.5% (4/32) of the isolates were resistant to only penicillin, but one isolate (1/32; 3%) showed resistance to the antibiotics penicillin, erythromycin, ampicillin, and oxacillin. PCR analysis revealed that 9.4% (3/32) of the isolates carried the mecA gene associated with methicillin-resistant Staphylococcus aureus (MRSA) isolates. One MRSA isolate was identified as a t008 spa type, and harbored a 26,974 bp-sized plasmid, which was the source of its resistance to penicillin, ampicillin, erythromycin, and oxacillin. The staphylococcal enterotoxin (SE) genes seg, sei, sek, seb, selm, and seln were also identified among the isolates, and mostly the antimicrobial and enterotoxin genes were carried on plasmids of the isolates. This study raises awareness on the continuous circulation of pathogenic microbes like S. aureus in retail poultry meat.